Maternal Serotonin: Shaping Developmental Patterns and Behavioral Strategy on Progeny in Molluscs - Voronezhskaya, Elena E. (Frontiers in Ecology and Evolution, 2021)
Serotonin is a well-known neurotransmitter and neurohormone regulating mood, sleep, feeding, and learning in high organisms. Serotonin also affects the embryonic events related to neurogenesis and maturation of hormonal systems, underlying organism adaptation to changing environment. Such serotonin-based mother-to-embryo signaling is realized via direct interactions in case of internal fertilization and embryonic development inside the mother body. However, the possibility of such signaling is less obvious in organisms with the ancestral type of embryogenesis and embryo development within the egg outside the mother body. Our data based on the investigation of freshwater gastropod mollusks (Lymnaea and Helisoma) demonstrated a correlation between seasonal variations of serotonin content within the female reproductive system, and developmental patterns and behavioral characteristics of progeny. The direct action of serotonin via posttranslational peptides modification – serotonylation – during early development as well as classical receptor-mediated effects underlies such serotonin-modulated developmental changes. In the present paper, I will shortly overview our results on freshwater mollusks and parallel the experimental data with the living strategy of these species occupying almost all Holarctic regions.